2016
DOI: 10.1007/s00330-016-4549-2
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive quantification of tumour heterogeneity in water diffusivity to differentiate malignant from benign tissues of urinary bladder: a phase I study

Abstract: Objectives To quantify the heterogeneity of the tumour apparent diffusion coefficient (ADC) using voxel-based analysis to differentiate malignancy from benign wall thickening of the urinary bladder. Methods Nineteen patients with histopathological findings of their cystectomy specimen were included. A data set of voxel-based ADC values was acquired for each patient’s lesion. Histogram analysis was performed on each data set to calculate uniformity (U) and entropy (E). The k-means clustering of the voxel-wise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
0
7
0
2
Order By: Relevance
“…Heterogeneity is an intrinsic characteristic of tumors; accurate assessment of tumor heterogeneity was of high clinical importance for tumor diagnosis, prognosis prediction, and treatment monitor (911). In our study, compared with mean k ep , 90th k ep showed better diagnostic efficiency and might be the independent differentiating variable for malignant OLPDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterogeneity is an intrinsic characteristic of tumors; accurate assessment of tumor heterogeneity was of high clinical importance for tumor diagnosis, prognosis prediction, and treatment monitor (911). In our study, compared with mean k ep , 90th k ep showed better diagnostic efficiency and might be the independent differentiating variable for malignant OLPDs.…”
Section: Discussionmentioning
confidence: 99%
“…However, only the mean value of the pharmacokinetic parameters was used as the differentiating metric, which would underestimate the heterogeneity of the tumors. Heterogeneity is an intrinsic characteristic of tumors, which makes tumor tissue different from normal tissue (9). Previous studies have indicated that assessment of tumor heterogeneity was very crucial for tumor diagnosis, prognosis prediction, and treatment monitor (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…While many studies reported mean ADC values from single slice-based ROIs, whole-lesion histogram analysis of ADC maps has been increasingly recognized for quantitative evaluation of intratumoral heterogeneity and tissue characteristics. One intrinsic feature of tumors is characterized by heterogeneity, which makes tumor tissue distinguished from normal tissue 26 . The whole-lesion method may better capture heterogeneous tumor areas with various diffusion characteristics demonstrated in the histogram and potential selective sampling bias could be decreased by measurement of whole tumor volumes 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Во многих исследованиях доказано, что данные методики визуализации следует относить к функциональным, то есть отражающим метаболизм и структуру опухоли [16,17]. Их объединяет возможность оценить опухоль и подлежащие структуры не только с помощью качественных критериев, но и количественных.…”
unclassified
“…В частности, с помощью ДКУ можно оценить микроциркуляцию (васкуляризацию и проницаемость), а с помощью ДВИ -диффузию протонов водорода. Оценка диффузии подразумевает уточнение степени свободы межклеточной жидкости и соответственно -плотности расположения клеток (клеточность, целлюлярность) [17]. Ограничение диффузии свойственно для опухолевой ткани, характеризующейся высокой клеточностью.…”
unclassified